Collective action to stop free grazing of livestock in Ethiopia - International Livestock Research Institute (International Livestock Research Institute, 2013)
Communities around Woreilu woreda in Kabe watershed agreed to stop free grazing after receiving advice by the project on “Enhancing communities’ adaptive capacity to climate-change induced water scarcity in drought-prone hotspots of the Blue Nile basin, Ethiopia” (a project implemented by ILRI, UNEP and Wollo university). Here, Awol Ali explains how adopting a 'Cut and Carry' system has benefited his livestock.